Implikasi Keberlakuan Kontrak Karya Pt Freeport Indonesia Pasca Undang-Undang No 4 Tahun 2009 Tentang Pertambangan Mineral Dan Batubara - Nefi, Arman; Malebra, Irawan; Ayuningtyas, Dyah Puspitasari (Jurnal Hukum & Pembangunan, 2018)
The most fundamental regulations on mining and coal industries are articulted in the Minerba Act of the previous regulation in Law Number 11 of 1967 concerning the Mining Basic Provisions. This regulation has amendedthe requirements of mining consession namely from Mining Authorization and Coal Contract of Work / Coal Contract of Work (KK / PK2PB) to become Mining Business License (IUP), Special Mining Business License (IUPK), and Mining Permit (IPR).This has had an impact on the existing mining contracts in Indonesia including PT Freeport's contract of work. This study discusses issues related to the concept of Contract of Work in Indonesia, legal position of Contract of Work (KK) of PT. Freeport Indonesia after the enactment of Law No. 4 of 2009, the necessity of transferring to Special Mining Business License (IUPK), and Legal Risks caused by the transfer of Contract of Work of PT. Freeport Indonesia to the Special Mining Business License (IUPK).